2022
DOI: 10.1136/bmjopen-2022-061921
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of ambulatory care among older adults: an exhaustive database study in an ageing city in Japan

Abstract: ObjectivesContinuity of care is a core dimension of primary care, and better continuity is associated with better patient outcomes. Therefore, care fragmentation can be an indicator to assess the quality of primary care, especially in countries without formal gatekeeping system, such as Japan. Thus, this study aimed to describe care fragmentation among older adults in an ageing city in Japan.DesignCross-sectional study.SettingThe most populated basic municipality in Japan.ParticipantsOlder adults aged 75 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…At the same time, patients are characterized by limited mobility, organic discomfort, and emotional agitation during infusion. Accompanying family members are prone to adverse emotions due to the limited things they can undertake, which makes it further difficult to carry out nursing work [ 4 ]. Infusion room nursing has the risk of different degrees and aspects of adverse events that affect the quality of nursing under multiple factors, and nursing management is an effective way to improve the quality and efficiency of nursing [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, patients are characterized by limited mobility, organic discomfort, and emotional agitation during infusion. Accompanying family members are prone to adverse emotions due to the limited things they can undertake, which makes it further difficult to carry out nursing work [ 4 ]. Infusion room nursing has the risk of different degrees and aspects of adverse events that affect the quality of nursing under multiple factors, and nursing management is an effective way to improve the quality and efficiency of nursing [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the nursing service strategies in the outpatient infusion rooms need to meet both wide applicability and high timeliness that can be completed within a limited working time, which undoubtedly increases the work difficulty of nursing staff in the rooms and brings certain safety risks to nursing safety [ 5 ]. Also, the failure to achieve the ideal nursing service work has led to a high incidence of nurse-patient disputes and other incidents [ 6 , 7 ]. Studies have shown that more than 80% of nurse-patient dispute incidents are caused by miscommunication and mostly occur between patients' families and nurses [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To address the issues raised by multimorbidity, it is essential to adopt the concept of integrated care that places patients at the center of their healthcare journey. However, the development of integrated care in Japan is limited compared to other countries as there is an absence of a formal gatekeeping system in the country [ 43 ]. Previously, most physicians in Japan underwent postgraduate training in specialized clinical departments, leading to an emphasis on specialization and a shortage of primary care physicians.…”
Section: Discussionmentioning
confidence: 99%